Beyond Crisis Talk: Making Time for Re-Searching New Narratives of Human Relations With Soil - Rita Giuffredi; Christian Colella; Laura Colucci-Gray; Andrea Caretto; Raffaella Spagna; Alba L'Astorina (Tecnoscienza)
In this paper, we focus on soil as a “contested terrain” emerging from the interplay of competing socio-political and cultural frames. Starting from the analysis of international reports on soil, we show how the urgency frame acts as a powerful discursive device that progressively reduces the inherent complexity of soil as a socio-ecological system, compressing the temporality of future perspectives and demarcating the inclusion/exclusion of non-human actors in soil communities. In the second part, we draw on examples of practice from our project BRIDGES to highlight possibilities for re-framing research as a “practice of attention” and experimenting with different temporalities and modes of relation with soil. Findings point to the need to address the fundamental questions that such an approach poses for all research communities. Bringing sedimented attitudes, perceptions, and ways approaching research to the surface, our experiences cast light on the importance of methodological choices for thinking differently about soil and about slowing down the narratives of research: not as a tool or resource, but as a shared process of crafting mutual relations amongst all kinds of practitioners, including more than humans.